In vivo monitoring of chemically evoked activity patterns in the rat trigeminal ganglion - Lübbert, Matthias; Kyereme, Jessica; Rothermel, Markus; Wetzel, Christian H.; Hoffmann, Klaus-Peter; Hatt, Hanns (Frontiers in Systems Neuroscience, 2013)
Albeit lacking a sense of smell, anosmic patients maintain a reduced ability to distinguish different volatile chemicals by relying exclusively on their trigeminal system (TS). To elucidate differences in the neuronal representation of these volatile substances in the TS, we performed voltage-sensitive dye imaging in the rat trigeminal ganglion (TG) in vivo. We demonstrated that stimulus-specific patterns of bioelectrical activity occur within the TG upon nasal administration of ten different volatile chemicals. With regard to spatial differences between the evoked trigeminal response patterns, these substances could be sorted into three groups. Signal intensity and onset latencies were also dependent on the administered stimulus and its concentration. We conclude that particular compounds detected by the TS are represented by (i) a specific spatial response pattern, (ii) the signal intensity, and (iii) onset latencies within the pattern. Jointly, these trigeminal representations may contribute to the surprisingly high discriminative skills of anosmic patients.